A novel technique for in situ uniaxial tests of self-assembled soft biomaterials. Issue 7 (18th February 2019) - Elhebeary, Mohamed; Emon, Md Abul Bashar; Aydin, Onur; Saif, M. Taher A.
Abstract : A novel method for the characterization of soft biomaterials and 3D tissues with living cells. Samples are self-assembled from a liquid droplet of the biomaterial on the testing stage. Abstract : We introduce a novel method to form 3D biomimetic tissues from a droplet of a cell–extracellular matrix (ECM) mixture on a sensor stage and to quantify tissue force and stiffness as a function of time under optical microscopes. This method exploits advances in micro–nano fabrication and capillarity for self-assembly and self-alignment of tissues on the stage. It allows simultaneous investigation of the microstructure of the tissue in situ while its mechanical response is quantified, thus linking tissue biophysics with physiology and revealing structural–functional properties of 3D tissues. We demonstrate the functionality of the stage by studying the mechanical behavior of different cell–collagen mixtures under mechanical, chemical and electrical stimulation. This includes force evolution in cell-free collagen during curing, myotubes differentiated from muscle cell–collagen/Matrigel ECM subjected to electrical stimulation, and fibroblast–collagen tissue subjected to cancer cell conditioned media (CM) and a Rho-kinase inhibitor, Y27632. Muscle contraction decreases with increasing frequency of electrical stimulation, and fibroblasts respond to CM by increasing contractility for a short time and completely relax in the presence of Y27632 but restore force with Y27632 washout.